Modeling and design of micro-structures: focusing on functionally graded materials and future prospects - Hirano, Tohru (Frontiers in Materials, 2025)
Functionally Gradient (Graded) Materials (FGMs) represent a class of advanced materials characterized by spatial distributions in composition and structure, resulting in corresponding changes in their material properties. The material properties depend on the micro-structures, which are also heavily influenced by fabrication processes. This paper provides an overview of the modeling and design of micro-structures in FGMs, highlighting historical developments, current technologies such as multi-scale modeling using the Finite Element Method, the evolution of modeling techniques, and the latest research trends, including the application of deep learning and AI. The advanced fabrication of FGMs by additive manufacturing will be covered in view of the resultant micro-structures. Furthermore, energy conversion FGMs will be investigated concerning the transport properties in grain boundaries and lattice structures.